Disease characteristics of psoriatic arthritis patients may differ according to age at psoriasis onset: Cross-sectional data from the psoriatic arthritis-international database - (:unkn) unknown (Clinical and Experimental Rheumatology S.A.S., 2021)
Objective To explore the impact of early versus late-onset psoriasis (PsO) on the disease characteristics of psoriatic arthritis (PsA) in a large-multicentre cohort. Methods The data from a multicentre psoriatic arthritis database was analysed. Patients were grouped according to age at psoriasis onset (early onset; <40 years of age, late-onset; >40 years of age) and disease characteristics of the groups were compared by adjusting for BMI and PsA duration, where necessary. Results At the time of analyses, 1634 patients were recruited [62.8% females; early onset 1108 (67.8%); late-onset, 526 (32.2%)]. The late-onset group was more over-weight [66.8% vs. 86.8%, p<0.001; adjusted for age - aOR 1.55 (1.11-2.20; 95% CI)]. The early onset group had more scalp psoriasis at onset (56.7% vs. 43.0%, p<0.001), whereas extremity lesions were more common in the late-onset group (63.8% vs. 74.2%, p<0.001). Axial disease in males and psoriatic disease family history in females were significantly higher in the early onset group [38.0% vs. 25.4%; p=0.005; adjusted for PsA duration - aOR 1.76 (1.19–2.62; 95% CI) / 39.5% vs. 30.1%; p=0.003; OR 1.51 (1.15–1.99; 95% CI), respectively]. Psoriatic disease activity parameters, patient-physician reported outcomes and HAQ-DI scores were similar in both groups. Conclusion Clinical features of PsA may be affected by the age at onset of PsO. Different genetic backgrounds in early and late-onset PsO may be driving the differences in psoriasis and PsA phenotypes. © Copyright CliniCal and ExpErimEntal rhEumatology 2021.
Keywords: Early; Late-onset; Psoriasis; Psoriatic arthritis